2015
DOI: 10.1111/eth.12437
|View full text |Cite
|
Sign up to set email alerts
|

Egg Cortisol Exposure Enhances Fearfulness in Larvae and Juvenile Rainbow Trout

Abstract: We investigated the effects of an early boost of cortisol exposure in rainbow trout (Oncorhynchus mykiss) eggs during fertilisation on subsequent behavioural responses when exposed to a sudden stimulus in larvae and juveniles. At 55 d post-fertilisation (dpf), treatment had no effect on high accelerations occurring after a sudden event. At 146 dpf, these high accelerations were more frequent in cortisol-treated fish than in controls. At 146 dpf also, swimming activity was increased in cortisol-treated fish bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Maternal cortisol plays an important organizational role during early development in fish, and cortisol treatment of eggs or embryos alters both physiology and behaviour of the developing young (e.g. Sloman, 2010;Burton et al, 2011;Li et al, 2012;Nesan and Vijayan, 2012;Colson et al, 2015;. However, programming of offspring is probably more complex than the action of cortisol alone, because previous studies have found effects of maternal stress even in the absence of increased embryo cortisol levels -for example, on egg size in Neolamprologus pulcher (Mileva et al, 2011) and on swim performance in Oncorhynchus nerka (Sopinka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal cortisol plays an important organizational role during early development in fish, and cortisol treatment of eggs or embryos alters both physiology and behaviour of the developing young (e.g. Sloman, 2010;Burton et al, 2011;Li et al, 2012;Nesan and Vijayan, 2012;Colson et al, 2015;. However, programming of offspring is probably more complex than the action of cortisol alone, because previous studies have found effects of maternal stress even in the absence of increased embryo cortisol levels -for example, on egg size in Neolamprologus pulcher (Mileva et al, 2011) and on swim performance in Oncorhynchus nerka (Sopinka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Using the continuous sampling method (when all of the activities that occur in a group of individuals are recorded for a specified time period), the following behaviours were recorded for each tank: stereotypies (repetitive swimming against the edge of the tank), acceleration bursts, and jumps. In addition, scan samplings (1/minute) (when the behaviour of all the individuals in a group are recorded at predetermined time intervals) were performed to measure the time spent inactive (as described in Colson et al (2015b)) and the time spent grouped as a shoal. The results are presented as percent of the observed time (over 10 scans) the fish were ‘inactive’ or ‘grouped’.…”
Section: Methodsmentioning
confidence: 99%
“…After solvent evaporation, steroids were suspended in 250 µl assay buffer. Cortisol was assayed in duplicate by a 3H cortisol radioimmunoassay as previously described (Auperin et al, 1997; Colson et al, 2015b).…”
Section: Methodsmentioning
confidence: 99%
“…adaptive) outcomes in terms of fitness in various taxa (Sheriff & Love, ). In fishes, it modifies anti‐predatory cues (Colson et al, ) and accelerates development until hatching (Kiilerich et al, ), possibly enhancing survival in dangerous contexts.…”
Section: Sampling Matrices To Extract Cortisolmentioning
confidence: 99%
“…It is now a well‐accepted acute stress indicator in the plasma but it does not necessarily reflect a state of chronic stress, because of HPI de‐sensitisation as a consequence of allostatic overload (Aerts et al, ). Nonetheless, it has been successfully applied by a variety of scientists, from physiologists (Auperin et al, ) to behavioural ecologists (Colson et al, ), in controlled environments and also in the wild (Geffroy et al, ; Love et al, ), to assess levels of stress in fishes. In addition, relation between the stress axis and neurogenesis (Sadoul et al, ; Sørensen et al, ), growth (Sadoul & Vijayan, ) and sex determination or sex‐change (Geffroy & Bardonnet, ; Goikoetxea et al, ; Olivotto & Geffroy, ) are now well described, highlighting the central role of cortisol in fish physiology and behaviour.…”
Section: Introductionmentioning
confidence: 99%